2022
DOI: 10.3390/en15020504
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Predictive and Prescriptive Offshore Wind Farm Operation and Maintenance

Abstract: Offshore wind farms are a rapidly developing source of clean, low-carbon energy and as they continue to grow in scale and capacity, so does the requirement for their efficient and optimised operation and maintenance. Historically, approaches to maintenance have been purely reactive. However, there is a movement in offshore wind, and wider industry in general, towards more proactive, condition-based maintenance approaches which rely on operational data-driven decision making. This paper reviews the current effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 162 publications
(180 reference statements)
0
11
0
Order By: Relevance
“…A condition-based maintenance strategy is characterised by components being continuously monitored and that maintenance actions are executed according to the condition. The predictive maintenance strategy is then, according to [4], described as the aim to predict failures before occurrence and that real-time data and predictive analytics are used, leading to a prescriptive maintenance strategy where recommended actions are provided based on the predictions.…”
Section: Maritime Logistics For Predictive Maintenance At Offshore Wi...mentioning
confidence: 99%
See 1 more Smart Citation
“…A condition-based maintenance strategy is characterised by components being continuously monitored and that maintenance actions are executed according to the condition. The predictive maintenance strategy is then, according to [4], described as the aim to predict failures before occurrence and that real-time data and predictive analytics are used, leading to a prescriptive maintenance strategy where recommended actions are provided based on the predictions.…”
Section: Maritime Logistics For Predictive Maintenance At Offshore Wi...mentioning
confidence: 99%
“…There exist several review papers on maintenance optimisation [11][12][13] [1], and one was found on predictive maintenance [4] at offshore wind farms. An early review of decision support models for offshore wind farms is provided in [14].…”
Section: Eera Deepwind Conference 2023 Journal Of Physics: Conference...mentioning
confidence: 99%
“…For example, the increasing maturity of machine learning approaches enables applications to improve the accuracy of demand, generation, and price forecasting [40]. Various other solutions have been proposed, such as intelligent energy management [42], demand response [43], operational optimization [44] and design optimization [45], fault prediction [46] as well as preventive and predictive maintenance for energy efficiency [47] and to extend the lifespan of machinery [48]. In the area of battery management, IoT and data science technologies enable numerous solutions to optimize battery manufacturing, operation and re-utilization [49].…”
Section: Digitalization Developments and Opportunities In Industrial ...mentioning
confidence: 99%
“…This is a maintenance technique specifically designed to reduce operational costs and asset risk, which aims at collecting and analyzing data concerning the condition of assets to prescribe relevant maintenance actions. To date, researchers have offered some valuable proposals from the management of heterogeneous multimodal asset data [3,4] and maintenance decisions making [5], covering areas such as wind farms [6], aviation industry [7], and residential buildings [8]. Choubey et al [9] presented a holistic end-to-end RxM framework, which integrates maintenance needs analysis, operational data, personnel scheduling, feedback information, and knowledge management.…”
Section: Introductionmentioning
confidence: 99%